Effect of Different Feed Additives on Ensiled Carrot Straw as an Animal Feed - B. Muwakhid; U. Kalsum; A. M. Wati (Universitas Andalas, 2021)
The problem that often comes by farmers is a shortage of feed in the dry season; one of the technologies that can be used is silage. Carrot straw (CRS) can be used as a silage material because of its abundance and nutritional value, which is good for the livestock. The purpose of this study is to know about the differences in the provision of feed additives, i.e., Lactobacillus casei-A, Lactobacillus plantarum, and Lactobacillus casei-B of the composition of CRS silage. Making silage by means of CRS was weighed, CRS was placed on a tray and added with feed additives based on experimental treatment, CRS was mixed thoroughly, stored, and closed in a laboratory-scale silo then placed at 26-28oC. CRS was given with three different feed additive treatments: CRS + 0.01% Lactobacillus casei-A, CRS + 0.01% Lactobacillus plantarum, CRS + 0.01% Lactobacillus casei-B. Ensiling was carried out for 21 days in four replications for each treatment, and each replication was made in duplicate. Statistical analysis after the data was obtained was using the SAS University application specification 4.0 red hat (64-bit) with code, and the difference between the treatment means (P<0.01) was determined using Duncan’s Multiple Range Test (DMRT). This study resulted that the different types of use of lactic acid bacteria had a significant effect (P<0.01) on organic matter content (OM), crude fiber content (CF), extract ether content (EE), nitrogen-free extract (NFE), neutral detergent fiber (NDF) and acid detergent fiber (ADF). This study concludes that the difference in the provision of feed additives affects the chemical composition of carrot straw silage. To sum up, Lactobacillus casei-A has a good value on NFE while Lactobacillus casei-B has a good value on OM, CF, EE, NDF, and ADF.